Influence of crosslinking agent and EVA residues on the properties of EVA boards used in the footwear industry (Research, Society and Development, 2022)
The ethylene-vinyl acetate (EVA) copolymer is a thermoplastic copolymer, with an elastomeric character, consisting of ethylene and vinyl acetate monomers. In the form of foams, it has been widely used in the footwear industry, especially in insoles. For the manufacture of an EVA foam, the main additives used are a crosslinking and expanding agent. The generation of waste from the footwear industry, specifically, the copolymer of ethylene and vinyl acetate (EVA), is related to the production process of shoe soles, insoles and insoles. Thus, the objective of this work is to study the concentration of crosslinking agent and EVA residue concentration in the properties of expanded EVA boards, seeking to understand how each one of them changes the final properties of the material. The friends were prepared in a bunbury mixer at 120ºC for 4 minutes and then homogenized in an open mixing cylinder for 2 minutes and molding of EVA plates was performed by thermal pressing at 165ºC. Expanded and were characterized by physical (density) and mechanical (permanent deformation by compression and hardness) tests, in addition to rheological tests. Rheometry results showing the addition of EVA residue and the increased concentration of crosslinking agent in them caused an increase in material viscosity during processing. The addition of residue and increase in the concentration of peroxide caused an increase in hardness and density density, the increase in density influenced lower values ​​of DPC.